2019
DOI: 10.7150/ijbs.35138
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of super enhancer downregulates the expression of KLF5 in basal-like breast cancers

Abstract: The transcription factor KLF5 (Krüpple-like factor 5) is highly expressed in basal-like breast cancer (BLBC), which promotes cell proliferation, survival, migration and stemness, serving as a potential therapeutic target. In the current study, a super-enhancer (SE) was identified to be located downstream of the KLF5 gene in BLBC cell lines, HCC1806 and HCC1937. JQ-1, a BRD4 inhibitor, inhibits the expression and activity of KLF5 in both HCC1806 and HCC1937 cells in a time- and dose-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…As for its potential clinical application, Chipumuro et al found cyclin-dependent kinase 7 (CDK7) inhibitor, THZ1, selectively downregulates SE-regulated MYCN overexpression and MYCN-driven transcription amplification in neuroblastoma (91). Similarly, other researchers revealed THZ1 suppressed SE-driven oncogenic transcriptional amplification in other cancers (92, 93).…”
Section: Crosstalk Between Sernas and Immune Checkpointsmentioning
confidence: 55%
“…As for its potential clinical application, Chipumuro et al found cyclin-dependent kinase 7 (CDK7) inhibitor, THZ1, selectively downregulates SE-regulated MYCN overexpression and MYCN-driven transcription amplification in neuroblastoma (91). Similarly, other researchers revealed THZ1 suppressed SE-driven oncogenic transcriptional amplification in other cancers (92, 93).…”
Section: Crosstalk Between Sernas and Immune Checkpointsmentioning
confidence: 55%
“…Previous studies indicated that many KLFs are involved in the development of breast cancer. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] In this study, using in silico analyses, we found that KLF16 might have tumor-promoting roles in breast cancer. KLF16 was first identified as a dopamine receptorregulating factor involved in the regulation of dopamine transmission in the brain.…”
Section: Discussionmentioning
confidence: 97%
“…In basal-like breast cancer, a super-enhancer drives KLF5 upregulation, which subsequently drives cell proliferation, migration, and stemness. 15 On the other hand, in estrogen receptorpositive (ER+) breast cancer, KLF5 inhibits cell proliferation by suppressing the transcriptional activity of ERα. 16 KLF6 inhibits estrogen receptor-mediated breast cancer cell growth via a c-Src-mediated pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The lentiviral pCDH-AKT plasmid was kindly provided by Dr. Binghui Li (Capital Medical University, Beijing, China), and lentiviruses were prepared according to published protocols 30 . MDA-MB-468 cells were infected with lentiviruses and the infected cells were selected by 1 µg/ml puromycin and were used for further analysis.…”
Section: Methodsmentioning
confidence: 99%